Analysis of the Socio-economic Contributions of Corcovado National Park and Caño Island Biological Reserve : The biological, archaeological, cultural richness of the South Coast mediated by the dynamism of its villagers, 2008 - Otoya Chavarría, Marco (2010)
Costa Rica has distinguished itself as a country that considers the nature and natural resources as vital factors to their socio-economic development. However, few studies-and partially-systematize and quantify the contribution of protected areas to economic and social development of the country. The National Parks and biological reserves are characterized by allowing both the development of a series of complex ecological functions like providing multiple socio-economic benefits. This study contributes by estimating the economic contribution of Corcovado National Park and Caño Island Biological Reserve to the socio-economic development of the country, the availability of information to improve the management of these conservation areas and their local communities and as well as to make recommendations in the field of environmental policy. This document is elaborated in the framework of the Project ―Systematization and Analysis of the Contributions of National Parks and Biological Reserves to the Economic and Social Development in Costa Rica, Benin and Bhutan‖, developed by CINPE and executed under the Program of South-South Cooperation (financed by the Kingdom of the Netherlands and administrated by Fundecooperación). The study is based on the approach known as cluster and value chain as a methodology to identify, systematize, estimate and quantify the socio-economic contribution of Corcovado National Park and Caño Island Biological Reserve for the country. We start from the premise and the fact that both conservation areas exist with very clear objectives for the conservation and protection of biodiversity and natural richness in the area, with the possibility of being visited and appreciated for recreational purposes under certain rules and restrictions. However, around them have been managed a series of activities that support the visitation, we refer to particular commercial activities that have direct and indirect relation to tourism. The cluster analysis is understood as a set or conglomerate of economic and social activities, in this case related to tourism, formed as a support structure among economic activities such as hotels, guides, restaurants, tour operators, related activities, etc., activities of own management from-MINAET SINAC, recreational activities and research and education, while promoting backwards and forwards chainings to other activities not exclusively at local level but also at regional and national level. Based on the cluster approach and on its conception was estimated a total economic contribution of both ASP to the socio-economic development in the amount of $91.590.697, 47 for 2008.